Temporal Relationship of Onset of Necrotizing Enterocolitis and Introduction of Enteric Feedings and Powdered Milk Fortifier - Vaks, Yana; Birnie, Krista L.; Carmichael, Suzan L.; Hernandez-Boussard, Tina; Benitz, William E. (American Journal of Perinatology, 2018)
Objective This article evaluates temporal relationships between onset of necrotizing enterocolitis (NEC) in preterm infants and introduction of enteral feedings or powdered human milk fortifier (HMF).Study Design This is a Poisson regression analysis of NEC cases at a single children's hospital between 1999 and 2009, using the self-controlled case series method to estimate adjusted daily event rate ratios (DERR) during postexposure intervals.Results Of 139 patients with a clinical diagnosis of NEC, 26 had early disease onset prior to initiation of feeding and were considered to be cases of spontaneous intestinal perforation (SIP). For the remaining 113 infants, the DERR for NEC onset were significantly greater on days for which infants were <14 days of age (DERR, 2.15; 95% confidence interval [CI], 1.22–3.79) or ≥31 weeks postmenstrual age (2.94; 95% CI, 1.51–5.83) or which fell within 14 days after initiation of enteric feeding (8.29; 95% CI, 4.73–14.53) or 4 days after introduction of HMF (12.32; 95% CI, 7.13–21.29).Conclusion There are strong temporal associations between onset of NEC and initiation of enteral feeding or powdered HMF in preterm infants.
Keywords: necrotizing enterocolitis; spontaneous intestinal perforation; preterm infant; feeding; milk fortifier; clinical practice